Strike before stroke : let's take the first strike against stroke! - Wong, Christina See Kei (2019)
This paper presents Strike Before Stroke, the first health communications campaign in Singapore that seeks to raise awareness of stroke among young adults aged 25 to 34. While stroke incidence among young adults is on the rise in Singapore, there has not yet been a local health communication campaign addressing this issue. Led by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, this campaign aims to raise the level of knowledge and perceived susceptibility of young adults towards stroke, and to improve their attitude and uptake towards stroke assessments. Both quantitative and qualitative research were used to assess the stroke literacy and stroke assessment behaviours in young adults.